2017
DOI: 10.1007/s11064-017-2261-5
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acids and Brain Metabolism

Abstract: This review aims to provide a historical reference of branched-chain amino acid (BCAA) metabolism and provide a link between peripheral and central nervous system (CNS) metabolism of BCAAs. Leucine, isoleucine, and valine (Leu, Ile, and Val) are unlike most other essential amino acids (AA), being transaminated initially in extrahepatic tissues, and requiring interorgan or intertissue shuttling for complete catabolism. Within the periphery, BCAAs are essential AAs and are required for protein synthesis, and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
134
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 105 publications
4
134
0
Order By: Relevance
“…As recently reported, ammonia stimulated the production of Gln, which subsequently enhanced the uptake of BCAAs into astrocytes . In the present study, NH 4 Cl‐treated cells showed higher levels of intracellular BCAAs.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…As recently reported, ammonia stimulated the production of Gln, which subsequently enhanced the uptake of BCAAs into astrocytes . In the present study, NH 4 Cl‐treated cells showed higher levels of intracellular BCAAs.…”
Section: Discussionsupporting
confidence: 85%
“…As recently reported, ammonia stimulated the production of Gln, which subsequently enhanced the uptake of BCAAs into astrocytes. [42][43][44] In the present study, NH 4 Cl-treated cells showed higher levels of intracellular BCAAs. Moreover, 3-methyl-2oxovaleric acid was significantly elevated in the NH 4 Cl-treated cells (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, many of the specific amino acids that were altered as a result of poly(I:C) play important roles in fetal brain development. 51 Previous studies have shown that decreased BCAA transport into the brain or increased BCAA catabolism within the brain is associated with ASD in both mice and humans. We also observed a significant decrease in the concentration of taurine, which is imperative to optimal proliferation, development, and maturation of brain cells.…”
Section: Ta B L E 2 Concentrations Of Free Amino Acids In Fetal Brainsmentioning
confidence: 99%